Variations in Optimism, Adjustment, Appraisals and Coping among the Students of Different Streams of Education (Indian Journal of Psychology & Education, 2015)
The present study was planned to assess the variations in optimism, adjustment and appraisals among the students of different streams of education. A sample of 159 students were divided into three groups (i.e different streams of education) with arts (n=21), commerce(n=51) and science (n=87) selected on the basis of availability which was taken from various cities across India such as Mumbai, Chandigarh and Rohtak. Age of the subjects ranged from 16 years to 18 years. There were 91 males and 68 females. These subjects were administered Life Orientation Test- Revised (LOT-R), Beck Depression Inventory , Satisfaction with life Scale, Pennebaker Inventory of limbic (PILL) languidness and Self Appraisals after the pre-board examination. Data were analysed by using Mean, SD and ANOVA. Further post hoc Duncan’s test was applied. Results revealed that depression was found to be higher among the students of arts when compared with commerce and science students.